Reality vs. Expectations of Assessment in STEM Education: An Exploratory Case Study of STEM Schools in Egypt - Mohamed Ali El Nagdi; Gillian H. Roehrig (MDPI AG, 2022)
In this exploratory case study, the assessment methods planned and used in Egyptian STEM schools were explored. The purpose of the study was to explore the relationship between the ideals provided in STEM education both from research and policy documents and the actual assessment strategies used both at the classroom and state level in order to understand the alignment between the proposed lofty goals of STEM and the modes of assessment actually used. Teachers in Egyptian STEM schools were surveyed and interviewed to explore this relationship. Samples of their assessments were also examined. Teachers were found to have been using two mutually exclusive models of assessment; a set of assessments at the disciplinary level and another set at multidisciplinary level including, but not restricted to, project and problem learning, inquiry, and reflective journaling. The study revealed partial alignment between expectations and reality of assessment in Egyptian STEM schools.